THE VALUE ORIENTATIONS OF ADOLESCENTS WITH DIFFERENT LEVELS OF EMOTIONAL INTELLIGENCE - Paladi Oxana; Cheptene Victoria (International Journal of Innovative Technologies in Social Science, 2024)
This article presents general characteristics of the concepts of emotional intelligence and value orientations from the perspective of several authors. There are presented some theoretical approaches with reference to the components of emotional intelligence and the types of value orientations. Moreover, in this paper some sequences of the research carried out on the subject of emotional intelligence and value orientations in adolescents are described. They directly relate to the hierarchies of terminal and instrumental value orientations of adolescents with different levels of emotional intelligence development: high level and low level. At a comparative level, priority values and values rejected by teenagers are presented, which denote different levels of emotional intelligence. The obtained results demonstrate that the value hierarchies in the experimental subjects are not identical. We emphasize that the research sample consists of 341 teenagers from the Republic of Moldova.